Cryptosporidium parvum infection alters the intestinal mucosa transcriptome in neonatal calves: implications for immune function - Veshkini, Arash; Dengler, Franziska; Bachmann, Lisa; Liermann, Wendy; Helm, Christiane; Ulrich, Reiner; Delling, Cora; Kühn, Christa; Hammon, Harald M. (Frontiers in Immunology, 2024)
One of the leading causes of infectious diarrhea in newborn calves is the apicomplexan protozoan Cryptosporidium parvum (C. parvum). However, little is known about its immunopathogenesis. Using next generation sequencing, this study investigated the immune transcriptional response to C. parvum infection in neonatal calves. Neonatal male Holstein-Friesian calves were either orally infected (N = 5) or not (CTRL group, N = 5) with C. parvum oocysts (gp60 subtype IIaA15G2R1) at day 1 of life and slaughtered on day 7 after infection. Total RNA was extracted from the jejunal mucosa for short read. Differentially expressed genes (DEGs) between infected and CTRL groups were assessed using DESeq2 at a false discovery rate < 0.05. Infection did not affect plasma immunohematological parameters, including neutrophil, lymphocyte, monocyte, leucocyte, thrombocyte, and erythrocyte counts as well as hematocrit and hemoglobin concentration on day 7 post infection. The immune-related DEGs were selected according to the UniProt immune system process database and were used for gene ontology (GO) and pathway enrichment analysis using Cytoscape (v3.9.1). Based on GO analysis, DEGs annotated to mucosal immunity, recognizing and presenting antigens, chemotaxis of neutrophils, eosinophils, natural killer cells, B and T cells mediated by signaling pathways including toll like receptors, interleukins, tumor necrosis factor, T cell receptor, and NF-KB were upregulated, while markers of macrophages chemotaxis and cytosolic pattern recognition were downregulated. This study provides a holistic snapshot of immune-related pathways induced by C. parvum in calves, including novel and detailed feedback and feedforward regulatory mechanisms establishing the crosstalk between innate and adaptive immune response in neonate calves, which could be utilized further to develop new therapeutic strategies.